Permeation Redux: Thermodynamics and Kinetics of Ion Movement through Potassium Channels - Horn, Richard (The Biophysical Society, 2014)
The fundamental biophysics underlying the selective movement of ions through ion channels was launched by George Eisenman in the 1960s, using glass electrodes. This minireview examines the insights from these early studies and the explosive progress made since then.